River Water Quality Analysis Using RO Filtration - Vadivelu, Rhishwan; Hairol Akhma, Muhammad Amir Fitri; Tuan Masrohaizat, Tuan Muhammad Syafiq; Mohamed Nor, Mohd Hadri (Multidisciplinary Applied Research and Innovation, 2026)
This study focuses on the analysis of river water quality before and after undergoing filtration using a 5-stage reverse osmosis (RO) system. Access to clean and safe drinking water is essential for maintaining public health and quality of life. However, many communities face challenges due to polluted river sources, limited municipal water treatment, and dependence on bottled water. The water samples were evaluated based on key physicochemical parameters including Total Dissolved Solids (TDS), Electrical Conductivity (EC), pH, and physical characteristics such as appearance and smell. The filtered river water was also compared to commercial mineral water and municipal tap water to assess overall quality. From the result, it shows that the quality of filtered river water was improved. Unlike complex or energy-intensive treatment systems, this study highlights the effectiveness of a basic RO-based setup for field or domestic applications. By providing practical data and a comparison with standard water sources, this study promotes awareness of filtered river water as a reliable alternative and contributes to improving safe water access in rural or backup scenarios.